Evidence of reduced peripheral microvascular function in young Black women across the menstrual cycle - D`Agata, M. N.; Hoopes, E. K.; Berube, F. R.; Hirt, A. E.; Kuczmarski, A. V.; Ranadive, S. M.; Wenner, M. M.; Witman, M. A. (Journal of Applied Physiology, 2021)
Black women (BLW) have a higher prevalence of cardiovascular disease (CVD) morbidity and mortality compared with White women (WHW). A racial disparity in CVD risk has been identified early in life as young adult BLW demonstrate attenuated vascular function compared with WHW. Previous studies comparing vascular function between premenopausal WHW and BLW have been limited to the early follicular (EF) phase of the menstrual cycle, which may not reflect their vascular function during other menstrual phases. Therefore, we evaluated peripheral microvascular function in premenopausal WHW and BLW using passive leg movement (PLM) during three menstrual phases: EF, ovulation (OV), and mid-luteal (ML). We hypothesized that microvascular function would be augmented during the OV and ML phases compared with the EF phase in both groups, but would be attenuated in BLW compared with WHW at all three phases. PLM was performed on 26 apparently healthy premenopausal women not using hormonal contraceptives: 15 WHW (23 ± 3 yr), 11 BLW (24 ± 5 yr). There was a main effect of race on the overall change in leg blood flow (Delta LBF) (P = 0.01) and leg blood flow area under the curve (LBF AUC) (P = 0.02), such that LBF was lower in BLW. However, there was no effect of phase on Delta LBF (P = 0.69) or LBF AUC (P = 0.65), nor an interaction between race and phase on Delta LBF (P = 0.37) or LBF AUC (P = 0.75). Despite peripheral microvascular function being unchanged across the menstrual cycle, a racial disparity was apparent as microvascular function was attenuated in BLW compared with WHW across the menstrual cycle.